Failure Analysis on Fiber Reinforced Thermoplastic Pipe. Issue 1 (March 2021) - Song, Chengli; Liu, Xinbao; Bai, Zhenquan; Kuang, Xianren; Wang, Shuai
Abstract: In recent years, fiber reinforced thermoplastic pipe (FRTP) has been widely used in oil fields of China due to its excellent corrosion resistance and coiling performance. With the further expansion of application scope, some failure accidents have occurred. Based on the inspection of the wall thickness, chemical composition and physical properties of a failed FRTP in the western oilfield of China, the causes are systematically analyzed. The results show that the main cause of the sample fracture is the decrease of the strength of FRTP due to the oil and gas media constantly penetrate into the lining and reinforced layer during the long-term service. Moreover, it is found that the outer sheath is worn and penetrated to the reinforced layer which further reduces the bearing pressure performance of FRTP and finally causes the fracture failure.